-5(-12+3x)=-45

Simple and best practice solution for -5(-12+3x)=-45 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5(-12+3x)=-45 equation:


-5(-12+3x)=-45

We simplify the equation to the form, which is simple to understand
-5(-12+3x)=-45

Reorder the terms in parentheses
+(+60-15x)=-45

Remove unnecessary parentheses
+60-15x=-45

We move all terms containing x to the left and all other terms to the right.
-15x=-45-60

We simplify left and right side of the equation.
-15x=-105

We divide both sides of the equation by -15 to get x.
x=7

See similar equations:

| 36+x^2=-12 | | 40-3b=-b+6(3-4b) | | -2x^2-x-1=0 | | 3x^2-45+108=0 | | 2(3b-2)=3b+5 | | -s^2+4s-6=0 | | 11-4a=4 | | 8y+9=10+8y | | 14+3n=8n-3n-12 | | 5-2y+3+4y=8 | | -5(x+2)+8x=-2+3x-8 | | 9x-139=3x-13 | | -6(2+x)=4-8x | | (4x)=(x+120) | | 3(2x-7)-7(x-8)=x-7-6+4x | | (1+c^2)(4c^2+7c-3)=0 | | 15-(-4)=x | | 6(2x-9)=4+11x | | 18/7.5=x/5 | | 3x-y+z=1 | | -3x-5=6x-32 | | 13=2y-3y+4 | | 5x^2-10x-80=0 | | 2(w-3)=3(w-1) | | 7k^2-6k*3=3 | | 32/4=b+4/3 | | 80+6x=145+7x | | 8=8n-4(a+8) | | .125d+7=16 | | 16a^2+24a+9= | | 2x-3y+z=-3 | | -3x^2+11x+25=0 |

Equations solver categories